Time-dependent failure criteria for polymer matrix composites: a review - Rui Miranda Guedes (2010)
This article reviews several theoretical approaches for lifetime predictions proposed for polymer and polymer-based matrix composites. All these theories can be classified as global and homogenous approaches. Actually, regarding engineering applications, the global and homogeneous analyses are more convenient. Fracture mechanics, damage mechanics, and energy-based failure criteria are presented and illustrated with published experimental data.